2021
DOI: 10.1016/j.jbc.2021.100574
|View full text |Cite|
|
Sign up to set email alerts
|

The PorX/PorY system is a virulence factor of Porphyromonas gingivalis and mediates the activation of the type IX secretion system

Abstract: PorX/PorY is a two-component system (TCS) of Porphyromonas gingivalis that governs transcription of numerous genes including those encoding a type IX secretion system (T9SS) for gingipain secretion and heme accumulation. Here, an in vitro analysis showed that the response regulator PorX specifically bound to two regions in the promoter of porT , a known PorX-regulated T9SS gene, thus demonstrating that PorX/PorY can directly regulate specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…The PglZ domain is often found in the RR proteins of TCSs ( 11 )—including PorX, which is required for the activation of the T9SS ( 18 ). In an apparently unrelated context, proteins containing a PglZ domain are necessary for the BREX anti-phage defence system ( 7 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PglZ domain is often found in the RR proteins of TCSs ( 11 )—including PorX, which is required for the activation of the T9SS ( 18 ). In an apparently unrelated context, proteins containing a PglZ domain are necessary for the BREX anti-phage defence system ( 7 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In P. gingivalis , PorX has been associated with PorY ( 13 , 16 ), an orphan signalling HK with a periplasmic sensor domain. However, there is little phenotypic overlap between the Δ porX and Δ porY mutants ( 18 , 82 ), making it unlikely that a PorY/PorX TCS regulates the secretion of virulence factors. Even so, it is possible that PorX and PorY operate as a TCS that regulates T9SS activity in response to environmental cues in other Bacteroidetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To compensate for the lack of a DNA-binding domain, PorX interacts with and stabilizes the transcription factor SigP, which directly binds the promoter regions of T9SS genes (Fig. 1; Jiang et al, 2021;Yang et al, 2021;Kadowaki et al, 2016). While the precise signal triggering this pathway has yet to be identified, deletion of either porX or sigP in P. gingivalis, results in the downregulation of T9SS components and activity, and in impaired processing of gingipains, as well as decreased toxicity (Sato et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the P. gingivalis ATCC33277– genome encodes seven two-component signal transduction system (TCS) pairs of a response regulator and a histidine kinase traditionally involved in gene regulation on other organisms (13). Recently it has been reported that one of these TCS, PorX/PorY, responds to environmental heme and through the co-ordinate action of porX and sigP regulates transcription of the T9SS and heme accumulation and mutants defective in either porX or porY are attenuated in a mouse model of virulence (14, 15). However, given the magnitude of changes in response to the concentration of heme, there may be other mechanisms of heme regulated gene expression in P. gingivalis.…”
Section: Introductionmentioning
confidence: 99%